Звуки тишины: рассказы и очерки о природе / Олег Трушин - Трушин Олег Дмитриевич (Икар, 2019)
Экземпляры: ОБСЛ (20240816) / Инвентарный номер: 1129902 / Цена: / Сис.шифр: 84(2) / Авт.знак: Т 80 / ГРНТИ: 17 / ББК: 84(2=411.2)6-4